Psychophysiological compatibility of rhythmic gymnasts - Medvedeva, E.N.; Golub, Ya.V.; Ageev, E.V.; Baryaev, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the features of the psychophysiological compatibility of qualified athletes in rhythmic gymnastics group exercise teams with existing differences in the experience of joint sports activities. Methods and structure of the study. Two teams of female athletes of rhythmic gymnastics group exercises took part in the scientific work, having differences in the experience of joint sports activities: team No. 1 had no experience of joint sports activities; team No. 2 had performed together for 2 years. To determine the components of psychophysiological compatibility, a battery of tests was used to assess the response time and conduct the object in command mode. Results and conclusions. It revealed a shorter time for simple visual-motor reaction, reaction time to a moving object, the number of mistakes made in complex visual-motor reaction, and greater efficiency of joint object management for a team with experience in joint actions, which ensures the quality of competitive exercises.